Theorizing religious socialization: a critical assessment. Issue 2 (3rd April 2019) - Klingenberg, Maria; Sjö, Sofia
ABSTRACT: Religious socialization remains a widely used concept amongst scholars who direct attention to the social patterns that underline the formation of religious attitudes. This article presents contemporary conceptualizations of religious socialization and provides an overview of how the concept is used in empirical studies. As the article sets the frame for the thematic issue at hand, it contains a presentation of the research project that the findings reported depart from. In line with the findings reported in the articles, we argue for an expanded understanding of religious socialization, formulated as four points. Finally, a definition of religious socialization that accounts for these four points is proposed.